ADDENDUM TO: A Study on the Eigen Properties of the Coaxial Waveguide of Cylindrical Form - Kim, Yeong Min (Transactions on Engineering and Computing Sciences, 2023)
The physical properties of the dielectric cladding wrapping the cylindrical waveguide were investigated by finite element method. These properties are described by transverse electric and magnetic field modes. To obtain these results, the eigen matrix equation basing on the Helmholtz vector equation must be solved. But the size of this equation is too large to derive the results using a personal computer. Therefore, the eigen equation is compressed using the Arnoldi algorithm and after that the results are derived using the Krylov-Schur iteration method. The similarity transformation matrix to make this equation into the Schure form contains the desired eigenmode pairs of electric field and electric potential. As results, these are schematically represented with the electric field, 3-dimensional electric potential and electric potential contour.